Pengaruh DPK, NPF, dan Inflasi terhadap Penyaluran Pembiayaan UMKM di Bank Syariah - Agnina Ilma Nur Annisa; Diharpi Herli Setyowati; Ruhadi Ruhadi (Journal of Applied Islamic Economics and Finance, 2021)
This study analyzes the influence of Third Party Funds, Non Performing Financing and Inflation of the Micro, Small and Medium Enterprise Financing Allocation of Islamic Banking in Indonesia. Population of this study is Islamic Banking listing in OJK. Sample technique used in this research is saturated sampling. The data used in this study is secondary data published by OJK during the period 2014-2018. Analysis technique used in this research is multiple linear regression analysis, using the SPSS application program. Based on the result of the analysis with a significance level of 5%, the study shows the following result: DPK partially not have a significant influent on the Micro, Small and Medium Enterprise Financing Allocation. NPF and Inflation partially have significant effect on the MSME Financing Allocation. DPK, NPF, and Inflation simultaneously have a significant influent on MSME Financing Allocation. All the variables X contribute simultaneously to variable Y, based on the results of the analysis the coefficient of determination is 62,3%, and the balance is equal to 37,7% is influenced by other variables.